2017
DOI: 10.1016/j.ymben.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

13C metabolic flux analysis of three divergent extremely thermophilic bacteria: Geobacillus sp. LC300, Thermus thermophilus HB8, and Rhodothermus marinus DSM 4252

Abstract: Thermophilic organisms are being increasingly investigated and applied in metabolic engineering and biotechnology. The distinct metabolic and physiological characteristics of thermophiles, including broad substrate range and high uptake rates, coupled with recent advances in genetic tool development, present unique opportunities for strain engineering. However, poor understanding of the cellular physiology and metabolism of thermophiles has limited the application of systems biology and metabolic engineering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 60 publications
2
39
1
Order By: Relevance
“…Of the eight KEGG pathways -with significant over-representation of enzymes changing with temperature -four were previously identified as over-represented in metagenomic studies of high temperature habitats (Badhai, Ghosh, and Das 2015;Saxena et al 2016) : carbon fixation pathway in prokaryotes, pyruvate metabolism, methane metabolism and purine metabolism. The TCA cycle, another enriched KEGG pathway, is known to be extensively utilized in three thermophilic bacteria (Cordova et al 2017) . In my approach, by identifying pathways with enzymes whose occurrence strongly correlates with growth temperatures, I strengthen the argument that these pathways are under evolutionary pressure in temperature adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight KEGG pathways -with significant over-representation of enzymes changing with temperature -four were previously identified as over-represented in metagenomic studies of high temperature habitats (Badhai, Ghosh, and Das 2015;Saxena et al 2016) : carbon fixation pathway in prokaryotes, pyruvate metabolism, methane metabolism and purine metabolism. The TCA cycle, another enriched KEGG pathway, is known to be extensively utilized in three thermophilic bacteria (Cordova et al 2017) . In my approach, by identifying pathways with enzymes whose occurrence strongly correlates with growth temperatures, I strengthen the argument that these pathways are under evolutionary pressure in temperature adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Flux analysis of three extremely thermophilic bacteria indicated that the metabolisms of the studied thermophiles were highly distinct, with differences in such pathways as amino acid or NADPH metabolism (Cordova et al 2017) . However, a communality is that all three strains relied heavily on glycolysis and the TCA cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in sequencing techniques, genomic analyses, and metabolic analyses have aided species characterization by providing the functional output of microorganisms and revealing their genotype-tophenotype regulations. For some environments, the functional metabolisms of representative species (mainly thermophiles and mesophiles) have been characterized in detail (2)(3)(4)(5). For cold environments, few studies have addressed the metabolic pathways of cold-adapted microorganisms (psychrophiles) directly, the emphasis being on genomic and diversity analyses instead (6)(7)(8).…”
mentioning
confidence: 99%
“…FBA and TFA analysis were performed (64 tests for E. coli and 32 for T. thermophilus ), by assuming maximisation of biomass yield as the objective function. Results were tested against available experimental data ( 13 C-MFA (38, 39) and metabolomics (38)) by calculating the Pearson correlation coefficient, and Kendall’s W to determine the agreement between criteria (only for E. coli ). In addition, a MDF approach was tested against experimental metabolomics data to assess its predictive capabilities in comparison with mod-matTFA.…”
Section: Resultsmentioning
confidence: 99%
“…An approach improving the resolution consisting in also measuring MIDs from intracellular intermediates has been suggested (32), but it is not commonly performed (11). Hence, 13 C-MFA data for E. coli and T. thermophilus (38, 39) was assumed as the gold standard in this study, as stated above (15).…”
Section: Introductionmentioning
confidence: 99%